Jan Verschueren's Description of Yéi-Nan Culture - Verschueren, J. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1982)
Joannis Cornelis Verschueren (1905-1970) worked as a Roman Catholic missionary in southern Irian from 1931 until 1970. In the 1950s he wrote a number of papers on the Y